Variación climática y presencia de plagas en el cultivo de soya bajo condiciones ambientales de Babahoyo - Rodríguez Cabezas, Carlos Pedro (2013)
The present investigation work was carried out in the months of June - November of the 2011 in the experimental fields of the Ability of Agricultural Sciences - UTB, located in the Km. 7.5 of the road Babahoyo - Montalvo, belonging to the canton Babahoyo - County of Los Ríos. The place presents a climate of humid tropical type, with half temperature 25,6 ºC, precipitation of 2329.8 mm and a relative humidity of 82%. The floor is of plane topography, texture franc - loamy and regular drainage. The general objective of the investigation was: to relate the climatic variation of the area of Babahoyo with the presence of illnesses and insects in different siembra times and the specific objectives were: to know the climatic variation that prevails during the months of the soya cultivation in the area of Babahoyo; to determine that illnesses and insects impact in the soya production; to know the evolution of the illnesses and insects according to the siembra date and to relate the production with the grade of virulence of the illnesses and present insects.